2010
DOI: 10.1182/blood.v116.21.1620.1620
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler Measures In Patients with Sickle Cell Disease at High Risk for Stroke and Receiving Hydroxyurea: The HyRetro Ancillary Study.

Abstract: 1620 Children with sickle cell disease (SCD) and increased Transcranial Doppler (TCD) sonography velocity measures are at increased risk for stroke. Although chronic transfusion decreases this risk ten fold, this form of therapy is burdensome, and includes risk of iron overload. Although it has been established that the risk of stroke is still present even after 30 months of transfusion therapy, the total length of transfusion therapy required is not known. Hydroxyurea (HU) therapy is effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
76
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(76 citation statements)
references
References 0 publications
0
76
0
Order By: Relevance
“…In the previous version of this Cochrane Review (Wang 2013) the review authors identified a total of 89 references: 80 references related to three included trials (STOP 1998; STOP 2 2005; SWiTCH 2012) and nine to three ongoing trials (SCATE 2015; SIT 2014; TWiTCH 2016).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the previous version of this Cochrane Review (Wang 2013) the review authors identified a total of 89 references: 80 references related to three included trials (STOP 1998; STOP 2 2005; SWiTCH 2012) and nine to three ongoing trials (SCATE 2015; SIT 2014; TWiTCH 2016).…”
Section: Resultsmentioning
confidence: 99%
“…We identified two completed trials within 22 publications which were classified as ongoing trials in the previous version of this review (SIT 2014,TWiTCH 2016). We identified 60 citations related to previously included trials (STOP 1998; STOP 2 2005, SWiTCH 2012). We excluded two trials: one previously ongoing trial (SCATE 2015); and one additional trial at the full text stage (Bernaudin 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations